Perspektif Tafsir dari Segi Bentuknya - Afdhal Surya Hamid; Maya Sari; Akma Khairunnisa; Ghotan Rolandi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The Qur'an, as the guiding book for Muslims, contains profound meanings that have consistently attracted scholarly attention throughout history. To comprehend these meanings, various interpretive methods have been developed and categorized based on their forms: Tafsir bi al-Matsur, Tafsir bi al-Ra’yi, and Tafsir bi al-Isyari. This article explores the characteristics, methods, and contributions of each type of interpretation in understanding the Qur'an. Tafsir bi al-Matsur relies on the traditions of the Prophet, his companions, and successors, providing an authoritative foundation. Tafsir bi al-Ra’yi integrates reason and ijtihad to address contemporary challenges. Meanwhile, Tafsir bi al-Isyari emphasizes esoteric dimensions that are symbolic and spiritual in nature. This study reveals that these three forms of tafsir complement each other in bridging human understanding of the Qur'an and addressing the intellectual and spiritual needs of Muslims in various life contexts.